Linking Bank Credit with Farm Net Income: A Study in the North Bank Plains Zone of Assam - R.N. Barman (Ind. Jn. of Agri. Econ., 2016)
The study has tried to analyse the impact of bank credit on technology adoption and uplifting the farm net returns and also various constraints in linking credit with production of important crops and livestocks in the North Bank Plains (NBP) zone of Assam along with exploring the scope for innovations in harnessing the increasing credit demand potential. The study conducted during the year 2013-14 covered in total 110 households (55 beneficiary and 55 non-beneficiary) of Sonitpur and Lakhimpur districts of the zone to assess the impact of bank credit on technology adoption, farm net return and production constraints of important crops. A deterministic linear programming model is employed to develop optimum feasible plans for both credit beneficiary and non-beneficiary farms. The study indicate that in case of beneficiary farmers net return generated per rupee of working capital is more as compared to the non-beneficiary farmers. Even without allowing the existing resource base to change merely increasing the credit inflow substantial increase in the farm net returns is possible in the optimal plans.